Pelayanan Nasabah BRI Cabang Buntok Menggunakan Aplikasi Mobile Banking pada Tahun 2017 - Harlina Kurniaty (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
BRI mobile banking application is one of the indirect services by BRI to its customers, where the service only uses the application attached to the customer's mobile phone. The research on BRI's mobile banking application is aimed to learn and understand how to use BRI's mobile banking application facilities and analyze the factors that affect the effectiveness and efficiency of BRI's mobile banking facilities. The service quality factors used to see the effectiveness and efficiency in the use of BRI mobile banking applications include Tangibles/direct evidence, Reliability, Responsiveness, Assurance, and Empathy. The customers studied are as many as 10 BRI customers of Buntok branch of active BRI mobile banking users. The method of this research is Triangulation method. The result of the direct interview with 3 active customers of BRI mobile banking who work as Civil Servant, Private Officer, and Student, based on 5 service quality said that using BRI mobile banking is more effective and efficient than coming directly to Bank, and seen from four inhibiting factors of service can be concluded that service using mobile banking application have inhibiting factor in its service that is often difficult network and system interference.